In situ deposition of a personalized nanofibrous dressing via a handy electrospinning device for skin wound care. Issue 6 (22nd January 2016) - Dong, Rui-Hua; Jia, Yue-Xiao; Qin, Chong-Chong; Zhan, Lu; Yan, Xu; Cui, Lin; Zhou, Yu; Jiang, Xingyu; Long, Yun-Ze
Abstract : The in situ deposition of an electrospun antimicrobial nanofibrous dressing via a handheld portable electrospinning apparatus for skin wound healing is reported. Abstract : Current strategies for wound care provide limited relief to millions of patients who suffer from burns, chronic skin ulcers or surgical-related wounds. The goal of this work is to develop an in situ deposition of a personalized nanofibrous dressing via a handy electrospinning (e-spinning) device and evaluate its properties related to skin wound care. MCM-41 type mesoporous silica nanoparticles decorated with silver nanoparticles (Ag-MSNs) were prepared by a facile and environmentally friendly approach, which possessed long-term antibacterial activity and low cytotoxicity. Poly-ε-caprolactone (PCL) incorporated with Ag-MSNs was successfully electrospun (e-spun) into nanofibrous membranes. These in situ e-spun nanofibrous membranes allowed the continuous release of Ag ions and showed broad-spectrum antimicrobial activity against two common types of pathogens, Staphylococcus aureus and Escherichia coli . In addition, the in vivo studies revealed that these antibacterial nanofibrous membranes could reduce the inflammatory response and accelerate wound healing in Wistar rats. The above results strongly demonstrate that such patient-specific dressings could be broadly applied in emergency medical transport, hospitals, clinics and at the patients' home in the near future.